A Amnesty and Abolition: Between Political Reconciliation and Justice from an Islamic Legal Perspective: Amnesti dan Abolisi: Antara Rekonsiliasi Politik dan Keadilan dalam Perspektif Hukum Islam - Gunawan, Muhammad Safaat; Mujahidah, Nurul; Azizah, Nur; Putra M, Hilton Tarnama; Sofyan, Sofyan (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
The discourse on amnesty and abolition in Indonesia has tended to be understood merely as a political legal instrument oriented toward the interests of the state, when in practice there is a tension between the aspects of justice, political reconciliation, and the protection of human rights. The cases of granting amnesty to Hasto Kristiyanto and abolition to Thomas Trikasih Lembong show a gap between the normative basis of positive law and the need for equitable reconciliation. This study aims to analyze the concepts of amnesty and abolition not only as political products, but also as legal instruments that have moral and religious legitimacy. The method used is normative legal research with a legislative, conceptual, historical, and theological approach, supported by primary legal sources, secondary literature, and authoritative references to Islamic jurisprudence. The results of the study show that, conceptually, amnesty and abolition not only serve to ease political conflict, but also have relevance to Islamic legal values. Amnesty can be interpreted as a reflection of the principle of rahmah (mercy) and the restoration of substantive justice through forgiveness and reconciliation, while abolition is in line with the principle of daf‘ al-mafsadah (prevention of harm) as an effort to maintain social stability and national unity. The common ground between the two legal frameworks is that they both view amnesty and abolition not merely as political products, but also as means of achieving justice and national reconciliation. Amnesty and abolition in the perspective of Islamic law can also strengthen the legitimacy of Indonesian positive law while providing a more comprehensive legal protection framework. This study offers an integration of Islamic legal values with positive law in the context of transitional justice, thereby enriching the scientific discourse on the relationship between law, politics, and religion in conflict resolution and national reconciliation in the contemporary era.